Anticipating the Unknown: An Ethical Critical Study in Cormac McCarthy’s The Road - Jassim, Isra Hasan (Al-Adab Journal, 2022)
Human beings expect and anticipate the unknown, including wishes, ambition, and the future. At times, the future is imagined as bright and hopeful. At other times, the future is expected to be gloomy and ominous. Therefore, human beings deal with the future with fear and skepticism. These fears are justified given the circumstances in the present, including human conduct in general, the conditions of wars, and environmental changes.Since literature recalls the past and tackles the issues of the present, it also expects what will happen in the future by visioning what the future would be. The visions presented in literature motivate the reader to think of other possibilities for the future by amending the present. Usually the future is portrayed through literary works, such as: science fiction, but in Cormac McCarthy’s The Road, the future is presented to show the reader that the it is the outcome of the past and the present.The current paper is an ethical critical study of Cormac McCarthy’s The Road . It aims to explore the reasons that lead to a dark future in McCarthy’s The Road. The paper aims to approach The Road by using Ethical Criticism. The paper also investigates human’s reaction to these changes in the future.